Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Finanzas de la Facultad Jurídica, Social y Administrativa, 2023-2024 - Ortiz Abad, Yeleni Merced (2024)
The present research consists of analyzing the relationship between basic cognitive processes, specifically attention and memory, and reading comprehension levels in Finance students during the first academic cycle (2023-2024). A quantitative, correlational approach was adopted with a non-experimental cross-sectional design, using deductive-inductive, scientific- analytical and statistical methods. With a sample of 25 first cycle students. To collect data, thed2 attention test, the RIAS intelligence scale (memory subscale) and the Instrument to MeasureReading Comprehension in University Students (ICLAU) were used. The results indicate that96% of the students show a low level of attention; Regarding memory, 40% are at a low leveland 56% are at a medium level. Regarding reading comprehension, 44% are at a low level. Therefore, in attention and reading comprehension a value of Kendall's Tau-b of 0.232 was obtained; memory and reading comprehension, a value of Kendall's Tau-b of 0.310 was achieved, placing them according to Kendall's rank correlation coefficient, in a range of +0.2 to +0.39, indicating a low positive correlation between basic cognitive processes and reading comprehension. These results highlight the relevance of cognitive processes, especially attention and memory, in the reading comprehension of the students evaluated.